2013
DOI: 10.1371/journal.pone.0069105
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic Acid Increases Lignin Production and Inhibits Soybean Root Growth

Abstract: Cinnamic acid is a known allelochemical that affects seed germination and plant root growth and therefore influences several metabolic processes. In the present work, we evaluated its effects on growth, indole-3-acetic acid (IAA) oxidase and cinnamate 4-hydroxylase (C4H) activities and lignin monomer composition in soybean (Glycine max) roots. The results revealed that exogenously applied cinnamic acid inhibited root growth and increased IAA oxidase and C4H activities. The allelochemical increased the total li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Cinnamic acid is a known allelochemical that belongs to the class of auxin, which is recognized as plant hormones regulating cell growth and differentiation [31]. In the lignin biosynthesis pathway with cinnamic acid as precursor and 4H3MC as intermediate, coniferylalcohol dehydrogenase oxidizes coniferyl-alcohol to 4H3MC consuming NADP + [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamic acid is a known allelochemical that belongs to the class of auxin, which is recognized as plant hormones regulating cell growth and differentiation [31]. In the lignin biosynthesis pathway with cinnamic acid as precursor and 4H3MC as intermediate, coniferylalcohol dehydrogenase oxidizes coniferyl-alcohol to 4H3MC consuming NADP + [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that not even the largest accumulation of leaf Mn (9.08 mg kg -1 biomass) supply this nutrient to the soybean crop, which is in the range between 20 and 200 mg kg -1 (Galrão 2004), being detected symptoms typical of Mn deficiency, such as necrosis and chlorosis internerval (Dechen and Nachtigall 2006). In this scenario, the Mn deficiency causes damages in the chloroplast structure due to a reduction in the levels of the enzyme MnSOD (Allen et al 2007) and an increase in oxygen free radicals (Marschner 2012, Salvador et al 2013, affecting photosynthesis rate and reducing the amount of chlorophyll, which decreases the level of soluble carbohydrates in plants (Ndakidemi et al 2011), as observed for total chlorophyll, A and dry weight of shoot (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, shoots on the medium containing Zircon produced shortest roots compared with all other treatments. Recent research has shown that exogenously applied cinnamic acid, precursor of hydroxycinnamic acids, inhibited soybean root growth [15]. Addition of Melafen to medium also had positive effect on root formation but only one of five concentrations used, 10 −5 %.…”
Section: Discussionmentioning
confidence: 97%